Water Sources Inventory, Annotated Checklist, and Distribution of Water Sources Under Gelephu, Samtenling, and Dekiling Gewog in Sarpang District, Bhutan - Jigme Tenzin; Yeshi Yangdon; Karma Wangchuk; Pema Rinchen; Tashi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The Kingdom of Bhutan is endowed with abundant water resources. However, owing to rugged topography and associated climatic variations, accessibility remains a major challenge with communities facing seasonal and local scarcity of water. Generally, freshwater appears in the form of glaciers, lakes, wetlands, marshes, springs, and streams which support diverse life and livelihood. However, comprehensive inventories of water resources seem lacking in a water-rich country like Bhutan. Thus, water sources inventory was carried out using Focus Group Discussion and semi-structured questionnaires survey with 81 households (27 villages) from three highly populated gewog under Sarpang district in 2016 and collected the geo-coordinates (location) of each water source using Garmin GPS. The survey recorded a total of 104 perennial water sources from three gewogs under the district. Among the three gewogs, Samtenling and Dekiling have the highest water sources (n = 40) and Gelephu has the lowest (n = 24). While, in the case of source types, Samtenling gewog has the highest (n = 29), followed by Gelephu (n = 18) and Dekiling has the lowest (n = 14). Likewise, Dekiling has the highest number of streams (n = 24), followed by Samtenling (n = 9) and the lowest was Gelephu (n = 6). Therefore, periodic monitor of existing water sources, strengthening water governance, and adaptation of an integrated watershed management plan backed with detailed hydro-geological assessment covering entire watersheds are suggested for ensuring sustainable management of water sources, but also mitigates the climate change effects of these regions in the future.